2013
DOI: 10.1038/bcj.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Pomalidomide: the new immunomodulatory agent for the treatment of multiple myeloma

Abstract: In this report, we provide a comprehensive review on the preclinical and clinical investigations conducted in development of the next-generation immunomodulatory drug (IMiD) pomalidomide for the treatment of relapsed/refractory multiple myeloma (MM). We consulted PubMed, MEDLINE, ASH, ASCO annual symposium abstracts and http://clinicaltrials.gov/ for the purpose of this literature review. Twenty-six preclinical and 11 clinical studies were examined. These studies delineate the mechanisms of action of pomalidom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 46 publications
(46 reference statements)
3
66
0
Order By: Relevance
“…Lenalidomide-mediated inhibition of HRP was not concentration dependent (supplemental Figure 2B) and inhibited H 2 O 2 decomposition in clinically achievable concentrations. Pomalidomide was the most potent inhibitor, consistent with its perceived clinical potency 20 (Figure 2B-C; supplemental Figure 2A). Moreover, we also confirmed that lenalidomide inhibited intracellular H 2 O 2 decomposition in samples from MM patients (CD138 1 ) at a clinically achievable concentration ( Figure 2D).…”
Section: Lenalidomide Inhibits Intracellular H 2 O 2 Decomposition Insupporting
confidence: 59%
“…Lenalidomide-mediated inhibition of HRP was not concentration dependent (supplemental Figure 2B) and inhibited H 2 O 2 decomposition in clinically achievable concentrations. Pomalidomide was the most potent inhibitor, consistent with its perceived clinical potency 20 (Figure 2B-C; supplemental Figure 2A). Moreover, we also confirmed that lenalidomide inhibited intracellular H 2 O 2 decomposition in samples from MM patients (CD138 1 ) at a clinically achievable concentration ( Figure 2D).…”
Section: Lenalidomide Inhibits Intracellular H 2 O 2 Decomposition Insupporting
confidence: 59%
“…It differs from thalidomide by the presence of an additional amino group at the fourth position on the phthaloyl ring, and from lenalidomide by an additional oxo group on the phthaloyl ring (FIGURE 1) [5]. Pomalidomide has been approved by the FDA in the US as Pomalyst Ò (Celgene Corporation, Summit, NJ, USA) and by the EMA in EU as Imnovid Ò (Celgene Europe Ltd, Uxbridge, UK).…”
Section: Structurementioning
confidence: 99%
“…As a novel IMiD, pomalidomide inhibits the interactions between myeloma cells and bone marrow microenvironment, and decreases the production of TNF-α and other cytokines such as IL-6 [42]. Studies showed that pomalidomide potentiated the inhibitory effects on its target cytokines better than thalidomide, which resulted in improved therapeutic effects [43]. However, pomalidomide can potentially cause severe embryo-fetal toxicity and venous thromboembolism.…”
Section: New MM Drugs and Patents Under Development Or In Clinical Trialsmentioning
confidence: 99%